Learning subject matter through English as the medium of instruction: students' and teachers' perspectives - Floris, Flora Debora (Asian Englishes, 2014)
Many policy-makers are in favor of Content Language and Integrated Learning (CLIL) for this approach integrates both language and content. In Indonesia, CLIL is locally known as English as a medium of instruction (EMI) where content subjects are taught in English. This present study presents the results of implementing an EMI policy in a large college in Indonesia, a semester after the start of the implementation. The main objectives of the study were to seek the views of both the students and teachers regarding the use of EMI. Questionnaires, classroom observations, and interviews were used as the research instruments. The findings suggest that both students and teachers acknowledge the important role of English in the world. However, both reported a host of problems with the implementation of EMI. In this paper, I would also suggest ways to deal with these from both institutional and curricular perspectives.